One painting a day : a 6-week course in observational painting--creating extraordinary paintings from every day experience - Callaghan, Timothy (Timothy H.) (One a day, 2013)
"One Painting A Day offers you an inspiring six-week course exploring the timeless traditions of observational painting through daily experience and routine.This motivational guide is broken up into three parts to focus on the three major traditions of observational painting: still life, landscape, and portraiture. Each of the 42 daily exercises launches a small, immediate, and responsive painting based on a theme drawn from your daily experience. You will find suggestions on technique, approach, and materials for each day, while the "weekly lessons" explore a format or a rhythm for creating content, inspiring you to make the ordinary extraordinary as you create from every day experience. This beautiful collection of contemporary paintings serves as a workbook of ideas for aspiring artists, art students, professional designers, and art lovers alike"--